ANALISIS MAKNA UMMI DALAM ALQURAN DAN HADIS - Siregar, Dame (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2017)
Ummi meaning is the person who does not access the book as a guide or guidance diverse, not illiterate or not good at reading. The meaning of the linguist is contradicted by the life history of the Prophet in which he was sent to the Arabs who loved the loyal year-old poetry contest in suqul 'ukazh dzil Majinnah. The greatest poem is hung on the door of the Ka'aba called Syair Mu'allaqot. Suroh al-Ankabut verse 48 is clear that the Prophet Muhammad was good at writing. In the text of Yasin verse 2 and suroh alain that there are words tanzil and anzala and tasrifnya explain that the Koran descended from Alloh not the work of the Prophet Muhammad as a reason sebahagia ulama that the Prophet Muhammad is not good at writing so that people believe that the Qur'an is not made by Prophet Muhammad. Many of the Prophet's hadiths make it clear that the Prophet Muhammad sent letters to Yemen about faroid, diyat and other problems with his own hands